Placenta growth factor expression is correlated with survival of patients with colorectal cancer - Wei, S-C (Copyright 2005 by Gut, 2005)
Background: Overexpression of vascular endothelial growth factor (VEGF) correlates with vascularity, metastasis, and proliferation in colorectal cancer but the role of its homologue, placenta growth factor (PlGF), is unknown. The aim of this study was to evaluate expression and clinical implications of PlGF in colorectal cancer. Methods: We investigated 74 tumour/non-tumour pairs of colorectal cryosections. Clinical staging was based on the UICC-TNM classification. Expression levels of mRNA for PlGF and VEGF were analysed with quantitative real time reverse transcription-polymerase chain reaction. Proteins were analysed by immunohistochemical staining and enzyme linked immunoabsorbant assay. Analysis of the differences in PlGF and VEGF levels between tumour and non-tumour tissues in the same patient were performed by paired t test; differences between localised and advanced disease patients by the Mann-Whitney, χ(2), and Fisher’s exact tests and survival curves by the Kaplan-Meier method. Results: Expression levels for both growth factors were significantly higher in tumour than in non-tumour tissues (p⩽0.001). The ratio of PlGF expression in tumour to non-tumour in the advanced disease group was significantly higher than for the localised disease group (p = 0.009). Patients with more tumour PlGF mRNA had shorter survival (p = 0.028). The majority of PlGF was expressed in tumour cells. Conclusions: Our results suggest that PlGF expression correlates with disease progression and patient survival and may be used as a prognostic indicator for colorectal cancer.